Pharmacological Evaluation of Melanocortin 2 Receptor Accessory Protein 2 on Axolotl Neural Melanocortin Signaling - Wang, Xiaozhu; Xue, Song; Lei, Xiaowei; Song, Wenqi; Li, Lei; Li, Xuan; Fu, Yanbin; Zhang, Cong; Zhang, Hailin; Luo, Yao; Wang, Meng; Lin, Gufa; et al. (Frontiers in Endocrinology, 2022)
The Melanocortin-3 receptor (MC3R) and Melanocortin-4 receptor (MC4R), two members of the key hypothalamic neuropeptide signaling, function as complex mediators to control the central appetitive and energy homeostasis. The melanocortin 2 receptor accessory protein 2 (MRAP2) is well-known for its modulation on the trafficking and signaling of MC3R and MC4R in mammals. In this study, we cloned and elucidated the pharmacological profiles of MRAP2 on the regulation of central melanocortin signaling in a relatively primitive poikilotherm amphibian species, the Mexican axolotl (Ambystoma mexicanum). Our results showed the higher conservation of axolotl mc3r and mc4r across species than mrap2, especially the transmembrane regions in these proteins. Phylogenetic analysis indicated that the axolotl MC3R/MC4R clustered closer to their counterparts in the clawed frog, whereas MRAP2 fell in between the reptile and amphibian clade. We also identified a clear co-expression of mc3r, mc4r and mrap2 along with pomc and agrp in the axolotl brain tissue. In the presence of MRAP2, the pharmacological stimulation of MC3R by α-MSH or ACTH significantly decreased. MRAP2 significantly decreased the cell surface expression of MC4R in a dose dependent manner. The co-localization and formation of the functional complex of axolotl MC3R/MC4R and MRAP2 on the plasma membrane were further confirmed in vitro. Dramatic changes of the expression levels of mc3r, mrap2, pomc and agrp in the fasting axolotl hypothalamus indicated their critical roles in the metabolic regulation of feeding behavior and energy homeostasis in the poikilotherm aquatic amphibian.